Biological and Catalytic Activities of Green Synthesized Silver Nanoparticles from the Leaf Infusion of Dracocephalum kotschyi Boiss. Issue 2 (4th November 2020) - Chahardoli, Azam; Qalekhani, Farshad; Shokoohinia, Yalda; Fattahi, Ali
Abstract: The discovery and development of active compounds to eliminate drug resistance and side effects is a crucial process. In this study, the leaf infusion of Dracocephalum kotschyi Boiss as a novel green alternative is used to synthesize silver nanoparticles (Drac‐AgNPs). Antibacterial, cytotoxicity effects, hemocompatibility, and the catalytic properties of these nanoparticles are evaluated. The synthesis of Drac‐AgNPs is confirmed by UV–vis spectroscopy, X‐ray diffraction, Fourier‐transform infrared spectroscopy, and transmission electron microscopy, where Drac‐AgNPs are spherical, with a size range of 5–63 nm. Their IC50 values against H1299 and MCF‐7 cell lines are above 50 and 100 μg mL −1, respectively. Drac‐AgNPs are effective against an inclusive range of the gram‐positive and gram‐negative bacteria, that is, Staphylococcus epidermidis, Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Serratia marcescens, and Pseudomonas aeruginosa, and a low hemolytic effect makes them an exceptional AgNP with a great hemocompatibility. They show a moderate catalytic‐effect in terms of removing methylene blue, with 67% degradation. Altogether, Drac‐AgNP, as a multi‐tasker material, shows potential for the prevention and treatment of infections and photothermal/chemotherapy of cancers. Abstract : In this study, the biological effects of green synthesized silver nanoparticles (19.41 nm) using a leaf infusion of Dracocephalum kotschyi (Drac‐AgNPs) are evaluated. Hemocompatible Drac‐AgNPs with a low hemolytic effect are effective against H1299 and MCF‐7cancer cell lines and bacterial strains of Escherichia coli, Bacillus subtilis, and Staphylococcus aureus . They have a moderate catalytic effect on removing methylene blue.